Evaluate the following expression for x = −2 and y = 3: 5xy − 3x
You are given both unknowns in this situation so you can take advantage of this by doing what is called: "plug and chug." Replace x and y in your expression with their respective values. Observe:
5(-2)(3) - 3(-2) = 5(-6) - (-6) =-6(5-1) = -24
Did that help out? Best me please? Thank you!
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?